The Verbal Irony found in English Novel “Twilight” - Ekasani, Kadek Ayu (Humanis; Vol 27 No 4 (2023), 2023)
Talking irony as one of the figures of speech has been commonly discussed not only in daily conversation but also in social media, contemporary fiction, and different works of literature. However, the study of irony itself is not widely discussed in the novel. This study aims to find the verbal irony that occurs in the novel and in what situations it occurs. The data were taken from the novel “Twilight” written by Stephenie Meyer. The theory is adapted from Winokur (2007) about the definition of verbal irony. This study uses a qualitative approach and data are collected by note-taking and classified into the types of irony. The findings of this study, there are 14 data of verbal irony occur in this study. This study also found that the ironic criticism in the novel appears to minimize the negative meaning of the message. So, it may reduce the level of criticism for the addressee to save face. Explaining Verbal Irony in the Novel is really different from what we communicate in real situations. We have to read the whole text to find the implicit meaning of the irony. For the next study, we can analyze the comparison between irony and humor in literary work, such as novels to have more sight into those signals.